MAKNA SIMBOLIK UPACARA MANGONGKAL HOLI BAGI MASYARAKAT BATAK TOBA DI DESA SIMANINDO KECAMATAN SIMANINDO KABUPATEN SAMOSIR PROVINSI SUMATERA UTARA - Putri, Fransiska Dessy; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Mangongkal holi is digging up bones deceased, which is the cultural heritage of the batak toba. In the caremony there mangongkal holi aspects rich symbolic meaning. The study aims to determine the meaning of inferensial, meaning significance, and meaning intensional.This study used a qualitative descriptive method of data collection techniques of observation, interviews, and dokumentansi. The data obtained are then processed to be reduced, resulting conclusions are presented to the public. Informants in this study were four based on purposive sampling method that researchers use. As for the examination of the validity of the data the researcher used the extension of participation and triangulation techniques.The results showed that the inferensial meaning for the people Batak Toba tin the village Simanindo Subditrict Simanindo District of North Sumatera Province consists of Martonggoraja, The event includes mangongkal holi ulos panampin, mangombak, lime water, and turmeria, with colth, ampang, and After the went of grave. Meaning of significance at a caremony in the form of mangongkal holi meaning of Relegious values can not be separeted from th symbois used include worship and ulos,Social values wich include martonggoraja, lime water, with cloth, stone na pir, and siaughter a buffalo, Interpreted from the chairman of the village cutomary Simanindo. Mangongkal holi caremony intensional meaning in the form of motivation and feeling.